Can Exclusive Breastfeeding Prevent Stunting in Lower Middle-income Countries (LMIC)?: A Systematic Review - Rhisma Nasita Sianti; Martha Irene Kartasurya; Apoina Kartini (International Journal of Integrative Sciences, 2024)
Stunting, a nutritional concern, exerts adverse effects by influencing the physical and functional attributes of a child's body, contributing to elevated rates of child morbidity. Globally, the prevalence of stunting remains considerably high, registering at 22.2% in 2017, with approximately 55% of affected children in Asia and 39% in Africa. To Evaluate the connection between exclusive breastfeeding and stunting rates in lower middle-income countries. The research design was a systematic review. Article searches were conducted using Google Schoolar, Pubmed, Science Direct, and Scopus databases. The keywords used were "Exclusive Breastfeeding OR Lactation AND Stunting" and "Exclusive Breastfeeding OR EBF OR Lactation AND Stunting". Inclusion and exclusion criteria were used when selecting article titles and abstracts. The study encompassed a total of 9,949 and 16 articles for analysis. Exclusive breastfeeding provides adequate calories to fulfill the growth requirements of toddlers. Consequently, toddlers who do not exclusively breastfeed are at a higher risk of experiencing stunting. Among the thirteen articles examined in this research, an association between exclusive stunting and breastfeeding was consistently observed. Conversely, three articles conveyed no discernible correlation between exclusive breastfeeding and stunting. Furthermore, these articles highlighted the limited advantages of exclusive breastfeeding in preventing stunting. Toddlers who were not exclusively breastfed exhibited a higher probability of experiencing stunted growth, demonstrating a clear connection between the occurrence of stunting and exclusive breastfeeding